Elucidation of efficient photosynthesis in plants with limited iron. Issue 5 (2nd November 2022) - Higuchi, Kyoko; Saito, Akihiro
ABSTRACT: Plants allocate large proportions of nitrogen (N) and iron (Fe) – principal elements in the photosynthetic electron transport system – to leaf chloroplasts. Although the molecular mechanisms to overcome N deficiency have been intensively studied, the acclimation of photosynthetic apparatus to Fe deficiency in higher plants remains to be further investigated. We previously reported about effective strategies in the chloroplasts of an Fe-deficiency-tolerant crop, barley, which allow photosynthesis under Fe-deficient conditions, not relying solely on Fe acquisition via the roots. The Fe-deficient barley leaves employ at least two strategies, viz., induction of thermal dissipation of absorbed light energy via Lhcb1 phosphorylation, which is maintained stably over Fe-deficiency periods regardless of light conditions, and improved electron flow in or around photosystem I through protein complexes with unknown composition. Previous studies have focused on healthy leaves from which chloroplasts can easily be isolated or on model organisms, such as Arabidopsis and cyanobacteria, to demonstrate typical photosystem structures and photochemical reactions. By contrast, in non-model plants, atypical photosystem structures and compositions have been reported. These structures are generally important to adapt to stress conditions or specific niches. In this review, we elucidate the mechanisms of acclimation of barley photosystems to Fe deficiency and provide an overview of the modulations in the photosystems of other plants under various stress conditions.